PENGARUH E-WOM DAN MOTIVASI PEMBELIAN TERHADAP KEPUTUSAN PEMBELIAN BARANG VIRTUAL - Wirasatya, I Made Katana; Seminari, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024DO - 10.24843/EEB.2024.v13.i02.p04, 2024)
A purchase decision is an integrated process that is combined to evaluate two or more alternative behaviors and choose one of them. When a consumer chooses to buy a brand, he still has to carry out the decision and make the actual purchase.  The purposes of the study is to determines the effects of e-WOM and purchases motivation on purchasing decision by online game players, Seal Online Blade of Destiny with 100 respondents. The sample method used in this study is the saturated sampling technique. Data was collected through the distribution of questionnaires. Analysis technique used is path analysis. Result show e-WOM and purchases motivation have positive significants effects on purchasing decisions. This shows that the better e-WOM and the motivation, the more purchasing decisions was made